Out of weakness: the 'educational good' in late antiquity. (2nd April 2016) - Allen, Ansgar
Abstract: This paper explores the nature of the educational good as it appears in late antiquity, arguing that the 'good' variously promised by education is in a state of perpetual deferral. This extends the tradition of ancient Greek philosophy where wisdom is to be forever approached but never realised. Three exemplary cases are considered: the educational good as it appears under the auspices of the Roman tutor; as it is manifested in Christian baptismal practices; and as it is practiced in early Christian monasticism. To lure willing subjects into an educational relationship whose fruits will ultimately never be realised, the educator must respectively employ techniques of seduction, suspicion and diversion.